Time-Resolved Visual Chiral Discrimination of Cysteine Using Unmodified CdTe Quantum Dots - Forough Ghasemi (Nature Portfolio, 2017)
Abstract Herein, we demonstrate a simple yet novel luminescence assay for visual chiral discrimination of cysteine. Thioglycolic acid (TGA)-capped cadmium-telluride (CdTe) quantum dots (QDs) exposing green emission were directly synthesized in aqueous solution. The interaction between cysteine molecules and CdTe QDs induced the aggregation of QDs via hydrogen bonding. As a result of electronic coupling within these aggregates, a redshift both in the absorption and emission spectra of QDs occured. The difference in the kinetics of the interactions between L- and D-cysteine with CdTe QDs led to chiral recognition of these enantiomers. Addition of D-cysteine to CdTe QDs in a basic media caused a green-to-yellow color change, while no color alteration in QDs emission was observed in the presence of L-cysteine after 2 hours. Notably, the QDs used in the proposed assay are free from any labling/modification, which makes the present strategy highly attractive for sensing applications. Furthermore, the presented chiral assay is able to determine the enantiomeric excess (ee) of D-cysteine in the whole range of ee values (from −100% to 100%).